Simulation of the plasma jet with a dispersed phase in an axisymmetric chamber - Kravchenko, O.Yu.; Kurhanovich, E.V.; Marushchak, I.S. (Вопросы атомной науки и техники, 2012)
The injection of plasma flow with dust particles into axially symmetric chamber filled with neutral gas is investigated using computer simulation. Calculations were carried out at different plasma flow velocities and dust particles sizes. As a result, the spatial distributions of the plasma and dust component parameters were obtained in the chamber at different times from the start of injection. All held calculations based on hydrodynamic approximation of plasma (without taking into account the effects of turbulence and absorption of particles on the walls of vessel) and processed by method of large particles. It is shown that large dust particles are distributed in chamber along its axis. In this case a narrow plasma jet is formed in the chamber. Dust particles of small size also extend in a radial direction, forming a wave structure. In this case, it is observed a significant expansion of the plasma jet. С помощью компьютерного моделирования исследуется инжекция плазменного потока с пылевыми частицами в аксиально-симметричную камеру, заполненную нейтральным газом. Расчеты выполнены при различных скоростях инжекции струи и различных размерах пылевых частиц. Вычисления основаны на гидродинамическом приближении для плазмы и дисперсной фазы и проведены методом крупных частиц. Получены пространственные распределения параметров плазмы и пылевой компоненты в камере в разные моменты времени от начала инжекции. Показано, что пылевые частицы большого размера распространяются в камере вдоль ее оси. При этом в камере формируется узкая плазменная струя. Пылевые частицы малого размера распространяются также в радиальном направлении, образуя волновую структуру. В этом режиме наблюдается значительное расширение плазменной струи. За допомогою комп’ютерного моделювання досліджується інжекція плазмового потоку з пиловими частинками в аксіально-симетричну камеру, заповнену нейтральним газом. Розрахунки проведені при різних швидкостях інжекції струменю та при різних розмірах пилових частинок. Обчислення ґрунтуються на гідродинамічномунаближаннідля плазми та дисперсійної фази і проведеніметодом крупних частинок. Одержані просторові розподіли параметрів плазми та пилової компоненти в камері в різні моменти часу від початку інжекції. Показано, що пилові частинки великого розміру розповсюджуються в камері вздовж її осі. При цьому в камері формується вузький плазмовий струмінь. Пилові частинки малого розміру розповсюджуються також в радіальному напрямі, утворюючи хвильову структуру. В цьому випадку спостерігається значне розширення плазмового струменю.